Performance comparison of resin-infused thermoplastic and thermoset 3D fabric composites under impact loading - Shah, S.Z.H. (Elsevier Ltd, 2021)
In this paper, the impact performance of a novel resin-infused acrylic thermoplastic matrix-based 3D glass fabric composite (3D-FRC) has been evaluated and compared with thermoset based 3D-FRC under single as well as recurring strike low velocity impact (LVI) events. The single impact tests revealed that the thermoplastic-based 3D-FRC exhibits up to 45 reduced damage area and can have up to 20 higher impact load-bearing capacity (peak force). The damage mode characterization showed that damage transition energy required for micro to macro damage transition is 27 higher, and back face damage extension is up to 3 times less for thermoplastic-based 3D-FRC. Meanwhile, the recurring strike impact test highlights that the thermoplastic-based 3D-FRC experiences a 50 less damaged area, better structural integrity, and survived more strikes. The comparison of single and repeated LVI tests have also allowed us to present a design criterion for estimating the safe number of repeated LVI events for a given impact energy. The superior impact resistance of thermoplastic-based 3D-FRC is attributed to their higher interlaminar fracture toughness, a tougher fiber-matrix interface, matrix ductility, and unique failure mechanism of yarn straining, which is not present in thermoset composites. Â© 2020